Keberadaan BP4 Lampung Selatan dalam Mengatasi Perceraian pada Aparatur Sipil Negara (ASN) Tenaga Medis - Fairuz Salsabila; Qoiz Azizah Bin Has (Institut Agama Islam Negeri Metro, 2023)
As a marriage counselor, coach and preserver, the Advisory Board for the Development and Preservation of Marriage (s an important role in maintaining the integrity of the household. However, in reality BP4 still has not carried out its role and function optimally. This can be seen in divorce cases that have become a common problem in all circles of society. The purpose of this research is to find out why the existence of BP4 is unable to prevent divorce, especially the State Civil Apparatus in medical personnel. This research uses a qualitative descriptive method with a psychological approach. The results of this study indicate that the existence of BP4 can be said to be not well established. Although it has been established since about 60 years ago, in fact BP4 is still unable to prevent divorce. One of the reasons is because BP4 does not get material and non-material support from the government, so that in its movement BP4 experiences many limitations. Furthermore, the results of interviews and documentation related to divorce in medical personnel, show that infidelity, lack of physical and mental maintenance, quarrels and disputes, and not having offspring, are the background for medical personnel to divorce. Based on this explanation, it can be concluded that divorce that occurs in medical personnel has similarities to divorce that occurs in society in general. This shows that divorce is not related to a profession.